Assessment of plant growth promoting activities of five rhizospheric Pseudomonas strains. (October 2018) - Georgieva, Teodora; Evstatieva, Yana; Savov, Valentin; Bratkova, Svetlana; Nikolova, Dilyana
Abstract: Many strains form different species of genus Pseudomonas are proven as important plant growth promoting rhizobacteria, because of their ability to solubilization of nutrients, producing of different metabolites and enzymes, antimicrobial activities, etc. The five rhizospheric Pseudomonas stains were characterized and identified as potential plant growth promoting rhizobacteria (PGPR) in the present study. Substrates assimilation profile (API 20NE) and 16S rRNA gene nucleotide sequences were used for identification of the four strains rhizospheric isolates. The studied strains demonstrate the specific composition of activities associated with direct and indirect mechanisms of plant growth promotion. The strain Ps. putida BTCC1046 showed a complex of PGP-activities including ability for P-solubilization, production of phosphatases and lytic enzymes, siderophore production and activity against two bacterial phytopathogens. The other strain Pseudomonas sp. 1S4 is considered as bioagent with strong antifungal activity. The investigated Pseudomonas strains have the potential to be used in agriculture as bioagents. Highlights: The Pseudomonas strains show the specific composition of PGP-activities. Ps. putida BTCC1046 have the potential to be used as PGP-rhizobacterial strain. Pseudomonas sp. 1S4 is considered as bioagent with strong antifungal activity.